KEANEKARAGAMAN JENIS TUMBUHAN PIONIR DI LAHAN BEKAS PENAMBANGAN EMAS TANPA IZIN DESA BUGANG KECAMATAN HULU GURUNG KABUPATEN KAPUAS HULU - Ruslaini, Ruslaini; Ekyastuti, Wiwik; Astiani, Dwi (JURNAL HUTAN LESTARI, 2021)
This study aims to obtain data on the diversity of pioneer plant species in the ex-illegal gold mining area from Bugang Village, Hulu Gurung District, Kapuas Hulu Regency. The research method used is a survey method with vegetation data sampling in the form of a single plot measuring 50 m x 100 m. Furthermore, 10 plots of 20m x 20m were made in single plots and the remaining 20m x 10m were 5 plots, 5m x 5m for saplings and 2m x 2m for seedlings and understorey 15 plots each. The results showed that there were 1,059 individual pioneer plants from 20 species and 11 families. The value of understorey vegetation density, seedling level and salpling level showed high criteria. The highest index of importance of understorey was 53.9% for Diplazium esculentum, 37.5% for Bellucia axinanthera and saplings 123% for Brookea tomentosa. The diversity index value (H ') for understorey, seedling level and sapling level has a value of <1. This value indicates that the ex gold mining site has a low level of diversity but still has a high level of control with a stable abundance of species and the number of individuals of each plant species that are evenly distributed. Keywords: Bugang Village, ex-illegal gold mining, pioneering plant, species diversityAbstrakÂ Penelitian ini bertujuan untuk memperoleh data keanekaragaman jenis tumbuhan pionir di lahan bekas penambangan emas tanpa izin Desa Bugang Kecamatan Hulu Gurung Kabupaten Kapuas Hulu. Metode penelitian yang digunakan adalah metode survei dengan pengambilan contoh data vegetasi berupa petak tunggal berukuran 50m x 100m. Selanjutnya dibuat 10 petak berukuran 20m x 20m dalam satu petak dan sisanya 20m x 10m ada 5 petak, 5m x 5m untuk pancang dan 2m x 2m untuk semai dan tumbuhan bawah masing-masing 15 petak . Hasil penelitian menunjukkan terdapat 1.059 individu dari 20 jenis dan 11 famili. Kerapatan vegetasi tumbuhan bawah, tingkat semai dan pancang termasuk dalam kriteria Â hutan yang baik. Indeks nilai penting tumbuhan bawah tertinggi adalah 53,9% untuk Diplazium esculentum, semai 37,5% untuk Bellucia axinanthera dan pancang 123% untuk Brookea tomentosa. Nilai indeks keanekaragaman tumbuhan bawah, tingkat semai dan pancang memiliki nilai <1. Nilai ini menunjukkan bahwa lokasi bekas penambangan emas memiliki tingkat keanekaragaman yang rendah namun masih memiliki tingkat kelimpahan jenis yang stabil dan jumlah individu tiap jenis tumbuhan yang tersebar merata. Kata kunci: Bekas penambangan emas tanpa izin, Desa Bugang, keanekaragaman jenis, tumbuhan pionir